Sleep Quality Affects Humoral Response in Recipients of Two-Dose Sinovac Vaccines - Hananta, Linawati; Larasati, Victoria; Surilena, Surilena (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
To curb the COVID-19 pandemic, the government distributed Sinovac vaccines. Sleep mediates immune function, including post-vaccination antibody response. This study aimed to analyze whether there was a difference in post-vaccination antibody levels in Sinovac vaccine recipients with poor and good sleep quality. This study used analytical observations of recipients of the two-dose Sinovac vaccine in 2021. Primary data included age, sex, the Pittsburgh Sleep Quality Index (PSQI) questionnaire, and post-vaccination IgG-SARS-CoV-2 antibody levels. The PSQI and IgG SARS-CoV-2 antibody levels were measured a month after the second vaccination. Participants with non-reactive antibody levels before the first vaccination were included, and participants with incomplete data were excluded. The Mann-Whitney test was used to look for associations between sleep quality and post-vaccination IgG SARS-CoV-2 levels. Univariate analysis showed that of 54 participants, 37 (68.5%) were male, and 28 (51.9%) had poor sleep quality. 15 participants (27.78%) were in the 36-45 age group, and median antibody levels in participants who received the second Sinovac Vaccine was 223.5 (199.01) units/mL. Post-vaccination IgG SARS-CoV-2 antibody levels were significantly associated with sleep quality (p=0.036).